The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5194/angeo-38-395-2020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the long-range transport of the 2015 Calbuco volcanic plume from ground-based and space-borne observations

Abstract: Abstract. This study investigates the influence of the 2015 Calbuco eruption (41.2∘ S, 72.4∘ W; Chile) on the total columnar aerosol optical properties over the Southern Hemisphere. The well-known technic of sun photometry was applied for the investigation of the transport and spatio-temporal evolution of the optical properties of the volcanic plume. The CIMEL sun photometer measurements performed at six South American and three African sites were statistically analysed. This study involves the use of the sate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 110 publications
(170 reference statements)
4
8
0
Order By: Relevance
“…It should be noted, however, that the daily AOD measured by MODIS appear to be lower than those obtained from ground-based observations by the sun-photometer. The obtained AOD distributions over São Paulo are in agreement with results reported by Bègue et al [12]. In their study, Bègue et al [12] found a mean bias error (MBE) between sun-photometer and MODIS observations of about 5.2%.…”
Section: Carbon Monoxide and Aod Variationssupporting
confidence: 90%
See 3 more Smart Citations
“…It should be noted, however, that the daily AOD measured by MODIS appear to be lower than those obtained from ground-based observations by the sun-photometer. The obtained AOD distributions over São Paulo are in agreement with results reported by Bègue et al [12]. In their study, Bègue et al [12] found a mean bias error (MBE) between sun-photometer and MODIS observations of about 5.2%.…”
Section: Carbon Monoxide and Aod Variationssupporting
confidence: 90%
“…The obtained AOD distributions over São Paulo are in agreement with results reported by Bègue et al [12]. In their study, Bègue et al [12] found a mean bias error (MBE) between sun-photometer and MODIS observations of about 5.2%. The AOD distribution at Santa Cruz (shown in Figure 5b) is higher than at São Paulo during August and September.…”
Section: Carbon Monoxide and Aod Variationssupporting
confidence: 90%
See 2 more Smart Citations
“…Long-range transport of volcanic aerosols in the Southern Hemisphere also was observed after the Calbuco VEI 4 eruption in Southern Chile in April 2015 [67][68][69] that resulted in a record size of the ozone hole over Antarctica in October 2015 [70]. The volcanic aerosol plume of Calbuco was mainly advected eastward in the Southern Hemisphere (across northeastern South America and South Africa) latitudinally bounded by the subtropical barrier and the polar vortex, but potentially reached polar latitudes about 4 months after the eruption (60 • S) [67,68]. Fernandoy et al [31] showed that LCL clearly has been influenced by air masses originating over the South American continent during the preceding years 2008-2014.…”
Section: Cross-correlation Analysismentioning
confidence: 86%